Geometry and sizing optimization of steel gable frames with tapered members. (August 2022) - Babaei, M.; Moharrami, H.
Abstract: Steel gable frames with tapered members are often used to cover large-span spaces. To save material, the members of these frames are often considered I-shaped with linearly tapered webs. However, more savings in the material may be obtained if the design of structures is optimized. Many attempts have been made to optimize the size of these kinds of frames. Since optimizing the geometry may result in more savings, in this research, besides optimizing the sectional properties of tapered members, the height of the crown of frames has been considered as a design variable and optimized. The optimality criteria (OC) algorithm is used to find the optimal design. The Leibnitz integral rule has been employed to overcome the difficulties that arise when doing sensitivity analysis of non-prismatic members. This research shows that: a) the use of the OC algorithm provides less weight design than the meta-heuristic algorithms. b) Considering the geometry variables makes the structure more optimal.